Effects of platforms' entry into own marketplace: Evidence from the mobile application market - Mark A. Jamison; Jakub Tęcza; Peter Wang (International Telecommunications Society (ITS), 2023)
We study the competition effects of platforms entering their own marketplaces in the context of mobile applications. Using a rich panel dataset of monthly observed applications on the most prominent mobile ecosystems, Apple and Android, we seek to understand how the launch of a new application by the platform owner affects consumers and third-party developers (developers). We find evidence that Apple's efforts have positive effects on developers and encourage innovation. But on the Android platform, introduction of a Google app decreases the number of users for developers' apps. This is likely a substitution effect rather than suppression as developers do not decrease their expansion on the Android platform. In general, we find evidence of platform vertical integration having positive impacts for consumers and developers, and only quite weak evidence of suppression.
Keywords: L86; L51; K21; 330; Platforms; competition; vertical integration; regulation; self-preferencing